DAMPAK PEMASARAN DIGITAL, LITERASI KEUANGAN, DAN KEWAJARAN HARGA TERHADAP KEPUTUSAN PEMBELIAN E-COMMERCE: PERAN MEDIASI DARI PERSEPSI NILAI - Agus Sunaryo; Eny Rachmawati; Adil Abdillah; Anna Kridaningsih (CERMIN: Jurnal Penelitian, 2025)
This study aims to examine the influence of digital marketing effectiveness, financial literacy, and price fairness perception on purchasing decisions in e-commerce, with perceived value as a mediating variable. A quantitative explanatory approach was employed. The sample consisted of 240 active e-commerce consumers in East Java, selected through simple random sampling. Data were collected using a five-point Likert scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that financial literacy significantly influences purchasing decisions both directly and indirectly through perceived value, with a negative effect. In contrast, digital marketing effectiveness and price fairness perception do not significantly affect purchasing decisions, either directly or indirectly. This indicates that higher financial literacy leads to more cautious and critical online consumer behavior, reducing impulsive purchases. The study highlights the role of financial literacy as a deterrent rather than a driver of digital consumption. This challenges traditional assumptions in consumer behavior models and calls for more transparency- and education-based e-commerce strategies. Future research should incorporate emotional factors and explore generational segmentation for deeper insights.